Proteksi Keamanan Data pada Quick Response (QR) Code - Abdur Rahman Harits Martawireja; Ridwan Ridwan; Angga Putra Hafidzin; Muhammad Taufik (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2021)
The implementation of Quick Response (QR) Code to share or store information increased widely. QR code can quickly provide a data or information such as contact person, plain text, URLs or other data by scan a QR code using smartphone camera. The raised of QR code implementation must to be follow by a level of data security. In this journal we will discuss a number of processes that can be used to improve data security in QR codes. In computer science there are several terms related to data protection i.e. Cryptography and Steganography. Cryptography focuses on securing information in the data exchange process. Steganography is a process of hiding information into an object that cannot be detected by anyone without a steganographic key. With these two processes i.e. cryptography and steganography or a combination of both, the data embedded in the QR code will not be easy to translate. The method that will be discussed is Speck Algorithm encryption and Advanced Encryption Standard (AES) with a combination of Steganography. Both methods succeed in converting confidential information into data that is not easily recognized. Confidential information that goes through a steganographic process becomes difficult to detect and gives the wrong message to a third party.